Comparison of big cat food habits in the Amazon piedmont forest in two Bolivian protected areas - Flores Turdera, Cecilia; Ayala, Guido; Viscarra, María; Wallace, Robert (THERYA, 2020)
The feeding habits of jaguar (Panthera onca) and puma (Puma concolor) were studied in the lower Tuichi, Hondo (PNANMI Madidi) and Quiquibey (RB Pilón Lajas) river valleys. A total of 122 large felid scats were collected and identified by an experienced local guide, with identifications later confirmed by morphometry. Of this total, 54 were also identified using associated tracks. For jaguar, prey species richness was 25 species considering all scats and 20 species only considering those scats associated with tracks. For puma, 28 and 22 prey species were obtained, respectively. The results indicate that there is low trophic niche overlap between both cats (0.46 and 0.44 respectively). The breadth of the trophic niche indicates that the jaguar is more specialized in its diet (0.28 and 0.42 respectively), mainly due to the high consumption of the white-lipped peccary (Tayassu pecari), which contributes significantly to jaguar prey biomass. The puma has a more generalist tendency (0.56 and 0.58 respectively), with the spotted paca (Cuniculus paca) the most frequently consumed prey and also contributing the most biomass. Despite the fact that both felines share most of their prey, jaguar and puma differ in the frequency of prey consumption.